Integrated Foliar Nutrients Application Improve Wheat (Triticum Aestivum L.) Productivity under Calcareous Soils in Drylands. Issue 21 (30th November 2021) - , Amanullah; Ilyas, Muhammad; Nabi, Haider; Khalid, Shah; Ahmad, Manzoor; Muhammad, Asim; Ullah, Saif; Ali, Izhar; Fahad, Shah; Adnan, Muhammad; Elshikh, Mohamed Soliman; Al-Tawaha, Abdel Rahman M.; et al.
ABSTRACT: The increase in world population especially in developing countries, where soil fertility and health are decreasing continuously, leading to soil degradation and desertification. Water scarcity in developing countries mostly under semiarid climates is one of the major problems that decrease crop growth and yield leading to food security problems. Integrated foliar nutrients management system could improve crop growth, yield and yield components of crops under arid and semiarid climates. There is lack of research to study the impact of integrated foliar nutrients management in field crops. Therefore, two field experiments were designed (2010–11 & 2012–13) with an objective to investigate the impact of integrated foliar nutrients management on wheat productivity under the semiarid condition. In experiment one, foliar spray of sole boron (B), sole zinc (Zn) and their combination (Zn + B) was applied at various growth stages (tillering, booting and anthesis) under irrigated vs. dryland wheat. It was concluded that integrated foliar application of Zn + B in one single split (0.2% each) or two equal splits (0.1% + 0.1% each) at booting stage increased yield and yield components of wheat. In experiment two, foliar macro nutrients [phosphorus (P) and potassium (K)] and micronutrients [boron (B) and zinc (Zn)] alone and in various combinations at boot and pre-anthesis stages was investigated. The results revealed that integrated use of foliar micronutrients (Zn+B) produced the highest spikes m −2, grains spike −1 and heavy seeds (grains). On the other hand, integrated use of foliar macro nutrients along with boron (P + K + B) produced longer spikes, more spikelets spike −1 and higher grain yield. Earlier foliar nutrients spray at boot stage increased wheat productivity.